PENGEMBANGAN WATERFRONT RESORT DI TRANQUIL TANJUNG AAN DI K.E.K MANDALIKA - Gatot Yoda Kusumah; Liong Ju Tjung; Priyendiswara A.B. Priyendiswara (Jurusan Arsitektur dan Perencanaan, 2019)
Indonesian tourism is an important sector in increasing state revenues. The tourism sector ranks third in terms of foreign exchange earnings. in 2014 The government established tourism as the leading sector in improving the economy to encourage regional development and employment. With the law of the Republic of Indonesia number 39 of 2009 concerning Special Economic Zones, hereinafter referred to as K.E.K is a region with a certain boundary with the jurisdiction of the Unitary State of the Republic of Indonesia which is determined to carry out economic functions and obtain certain facilities. Kab. Central Lombok is one of the places where there is a K.E, namely K.E.K Mandalika. In order to increase the income of the Lombok region where the development of K.E.K Mandalika is 1,175 ha and the author takes 21 ha of land at K.E.K Mandalika to develop a Resort with a waterfront concept in order to increase Lombok tourism. Based on background problems, the main underlyinh problem is the lack of supporting facilities to support activities in the Mandalika Special Economic Zone, therefore the need for accommodation in the Mandalika Special Economic Zone.Abstrak Pariwisata Indonesia menjadi sektor yang penting dalam peningkatan pendapatan Negara. Sektor pariwisata menempati urutan ketiga dalam hal penerimaan devisa. Pemerintah pada tahun 2014 menetapkan pariwisata sebagai leading sektor dalam peningkatan perekonomian untuk mendorong pembangunan daerah dan lapangan pekerjaan. Dengan adanya undang-undang Republik Indonesia nomor 39 tahun 2009 tentang Kawasan Ekonomi Khusus, yang selanjutnya disebut K.E.K (kawasan ekonomi khusus), adalah Kawasan dengan batas tertentu dengan wilayah hukum Negara Kesatuan Republik Indonesia yang ditetapkan untuk menyelenggarakan fungsi perekonomian dan memperoleh fasilitas tertentu. Kab. Lombok Tengah merupakan salah satu tempat dimana terdapat K.E.K yakni adalah K.E.K Mandalika. Guna dapat meningkatkan pendapatan daerah lombok dimana Pengembangan K.E.K Mandalika seluas 1.175 ha dan Penulis mengambil 21 ha lahan di K.E.K Mandalika untuk dikembangkan Resort dengan konsep waterfront guna dapat meningkatkan pariwisata lombok. Berdasarkan permasalahan latar belakang, permasalahan utama yang mendasar adalah belum adanya fasilitas pendukung untuk menunjang aktivitas di Kawasan Ekonomi Khusus Mandalika.